The Concept of Kelakat: Character Forming of Artists and Concepts of Art Creation - I Ketut Suteja (International Journal of Social Service and Research, 2023)
The concept of Kelakat is Balinese local wisdom made of woven bamboo in the shape of a square loaded with unique symbols and is interesting to study, because it contains the meaning of the combination of the + (Dik) sign. and the × (Widik) sign, the work rotates with each other. Dik symbol of the earth rotates to the left, and Widik symbol of the sky rotates to the right, its function is to maintain the balance of the world. The phenomenon is that the Balinese people make kelakat very skilled, but its value and meaning are not yet known. To prove cultural values ??in the concept of kelakat, it is necessary to research, philosophical theory, using qualitative descriptive methods, towards the formation of the character of the artist and the concept of creating works of art.